2020
DOI: 10.3390/metabo10030104
|View full text |Cite
|
Sign up to set email alerts
|

Important Considerations for Sample Collection in Metabolomics Studies with a Special Focus on Applications to Liver Functions

Abstract: Metabolomics has found numerous applications in the study of liver metabolism in health and disease. Metabolomics studies can be conducted in a variety of biological matrices ranging from easily accessible biofluids such as urine, blood or feces, to organs, tissues or even cells. Sample collection and storage are critical steps for which standard operating procedures must be followed. Inappropriate sample collection or storage can indeed result in high variability, interferences with instrumentation or degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 96 publications
(131 reference statements)
0
48
0
Order By: Relevance
“…The primary limitation of this study was that these results were based on blood samples collected at one time point because blood metabolome is dynamic and varies in response to exogenous metabolites, such as those supplied via diet, and changes in gene expression ( Smith et al, 2020 ). Therefore, as presented in this study, comparison of blood metabolome profiles among animals at a particular time point should be done using fasting plasma sample which is more reflective of modulations in endogenous metabolism ( Smith et al, 2020 ), and should be accompanied by gene expression analysis of interest, such as immune gene expression profile. It is important to note that this is not a validation study, but rather a study to initially identify potential mechanisms that cause divergence in ADG of beef cattle which may be used to inform future studies aimed at improving beef cattle productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The primary limitation of this study was that these results were based on blood samples collected at one time point because blood metabolome is dynamic and varies in response to exogenous metabolites, such as those supplied via diet, and changes in gene expression ( Smith et al, 2020 ). Therefore, as presented in this study, comparison of blood metabolome profiles among animals at a particular time point should be done using fasting plasma sample which is more reflective of modulations in endogenous metabolism ( Smith et al, 2020 ), and should be accompanied by gene expression analysis of interest, such as immune gene expression profile. It is important to note that this is not a validation study, but rather a study to initially identify potential mechanisms that cause divergence in ADG of beef cattle which may be used to inform future studies aimed at improving beef cattle productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The unfavorable issues concerning urine and feces are the possible discomfort experienced by patients and the complex chemical nature of them. Although breath has lower chemical complexity, various external factors can influence its composition, such as food remnants, hygiene products, metabolic products of colonizing oral bacteria and ambient air [ 57 , 58 , 59 , 60 ], turning challenging to address which fraction of it would represent blood-related biomarkers.…”
Section: Studies On Colorectal Cancer Metabolic Biomarkersmentioning
confidence: 99%
“…The composition of feces, urine and breath can also vary according to the physical state of the body, age, and general health. Hence, biomarkers found in these matrices can have multifarious origin that should be considered while establishing potential metabolic pathways of them [ 59 , 70 , 71 ].…”
Section: Studies On Colorectal Cancer Metabolic Biomarkersmentioning
confidence: 99%
“…Sample collection is also a crucial step to ultimately achieve the unbiased monitoring of a maximum of compounds and obtain a faithful picture of the metabolic state. This step encompasses different stages of the dedicated protocol and needs to be adapted to the model used for the study (blood, tissues, urine, feces, cells…) [ 32 ]. For all matrices, sample collection has to be performed as fast as possible to immediately block all enzymatic processes and prevent nonphysiological modifications of metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most often used method consists of a liquid extraction using different organic solvents, which are usually adapted for specific metabolite extractions [ 36 ]. Several studies have shown that each extraction solvent provides advantages and disadvantages for the recovery of different types of metabolites [ 32 , 37 ]. A fast-sampling method was developed by Martano et al [ 34 ] consisting of a fast and efficient washing of cells harvested on a coverglass, followed by a fast and reproducible metabolism quenching of enzymatic processes.…”
Section: Introductionmentioning
confidence: 99%